The Role of Peers in Students' Affective Development in Madrasah Ibtidaiyah in Social Studies Subjects - Fahmi Rohim; Riska Fitriani; Arif Abdurrahman (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to analyze the role of peer influence in the affective development of sixth-grade students in Social Science at Madrasah Ibtidaiyah Hidayatul Mubtadiin Jambi, focusing on social attitudes such as tolerance, cooperation, and social responsibility amid Indonesia's multidimensional crisis. Methodology: His research uses a descriptive qualitative method, collecting data through interviews and documentation from students, Social Science teachers, and homeroom teachers. The data were analyzed thematically using qualitative data analysis software. Main Findings: The study found that peers have a significant influence on students' affective development, particularly in tolerance, cooperation, and social responsibility. Students demonstrated tolerance by listening to differing opinions, helping peers in need, and participating in group cooperation, although some students remained passive. Novelty/Originality of this study: This study highlights the importance of peer influence in fostering social attitudes in the classroom. It provides new insights into how social interactions can affect students' affective development and offers recommendations for educators on managing social dynamics in the classroom to create a more positive learning environment.